2019
DOI: 10.1093/pcp/pcz116
|View full text |Cite
|
Sign up to set email alerts
|

Phototropins Mediate Chloroplast Movement in Phalaenopsis aphrodite (Moth Orchid)

Abstract: Chloroplast movement is important for plants to avoid photodamage and to perform efficient photosynthesis. Phototropins are blue light receptors in plants that function in chloroplast movement, phototropism, stomatal opening, and they also affect plant growth and development. In this study, full-length cDNAs of two PHOTOTROPIN genes, PaPHOT1 and PaPHOT2, were cloned from a moth orchid Phalaenopsis aphrodite, and their functions in chloroplast movement were investigated. Phylogenetic analysis showed that PaPHOT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…It has been reported that BL could induce photo-acclimation and thus assist plants’ tolerance to high light stress [ 15 , 16 , 17 ]. We also found that BL100 upregulated phototropins and significantly induced chloroplast avoidance in moth orchids [ 7 ]. This study further indicated that BL100 treatment for 12 days (T0) enhanced photo-acclimation in moth orchids.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that BL could induce photo-acclimation and thus assist plants’ tolerance to high light stress [ 15 , 16 , 17 ]. We also found that BL100 upregulated phototropins and significantly induced chloroplast avoidance in moth orchids [ 7 ]. This study further indicated that BL100 treatment for 12 days (T0) enhanced photo-acclimation in moth orchids.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf samples of the new fully expanded leaves (L1) were collected. The total RNA was extracted and DNase-treated, and qRT-PCR was performed for 40 cycles with KAPA SYBR FAST qPCR Master Mix (2×) Kit (Kapa Biosystems, Woburn, MA, USA), as descripted previously [ 7 ]. The primers used in this study for PCR are listed in the Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that blue light induces chloroplast movement in several monocot C 3 plants [11]. In CAM moth orchids, when blue light irradiation is above 25 µmol m −2 s −1 , chloroplasts start to show avoidance movement and significant chloroplast avoidance has been found in the strong blue light of 100 µmol m −2 s −1 [12]. When extra light has been absorbed, the plant will dissipate the excessive light energy through thermal dissipation via nonphotochemical quenching (NPQ) [7,13].…”
Section: Introductionmentioning
confidence: 99%